Introduction to Engineering Mathematics - Croft Anthony; Davison Robert; Hargraves Martin (Academic Press, Inc, 1995)
This text provides a well paced, mathematically sound and motivating foundation in applicable Mathematics. Dedications, Preface, Acknowledgements, Arithmetic, Symbols and Indices, Numbers and Sets, Working with Expressions, Using Formulae, Functions and Their Graphs, Common Engineering Functions, Further Properties of Functions and Their Graphs, Solving Equations and Inequalities, Angles and Their Trigonometric Ratios, Partial Fractions, Estimation, Logarithms and Exponentials, Triangles and Their Solution, Trigonometric Identities and Functions, Engineering Waves, Geometry of Straight Line, The Conic Sections, Mensuration, Sequences and Series, Change and Rates of Change, Some Rules of Differentiation, Integration - The Reserve of Differentiation, Areas Under Curves and Definite Integrals, Techniques of Integration, Matrices and Determinants, Vectors, An Introduction to Complex Numbers, Statistics and Probability, Appendices, SI Units and Prefixes, Unit Conversions, Solutions to Exercises, Index.